Pengaruh Transformasi Digital Dan Audit Syariah Terhadap Masa Depan Profesi Auditor - Desi Ratna Sari; Cris Kuntadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The aim of this research is to determine the influence of digital transformation in sharia auditing to build the future of the auditor profession with the latest technology. This research uses a qualitative approach. The results of the discussion show that digital transformation must ensure that the technology adopted continues to comply with sharia principles, both in product development and in carrying out transactions. Public awareness and understanding of technological innovation needs to be increased through digital literacy and education programs so that they can respond well to this transformation. There is a need for a clear and adaptive regulatory framework to support digital transformation and ensure that innovation remains in line with sharia values ​​and Islamic financial regulatory policies. In facing these changes, involving the community in the technology development process and listening to their needs is a must